2017
DOI: 10.7862/rm.2017.33
|View full text |Cite
|
Sign up to set email alerts
|

Badania Wybranych Wskaźników Skrawalności Podczas Frezowania Stopu Inconel 718 Narzędziami Ceramicznymi

Abstract: Agnieszka SKOCZYLAS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…They found that cutting speed and distance from the upper cut surface edge had the greatest impact on surface roughness. Skoczylas et al [28] also found that cutting speed had the greatest impact on surface roughness, regardless of the type of material. The surface roughness in the entry and exit zones was examined, and it was found that the entry zone was characterized by lower roughness (Ra parameter was analyzed).…”
Section: Introductionmentioning
confidence: 95%
“…They found that cutting speed and distance from the upper cut surface edge had the greatest impact on surface roughness. Skoczylas et al [28] also found that cutting speed had the greatest impact on surface roughness, regardless of the type of material. The surface roughness in the entry and exit zones was examined, and it was found that the entry zone was characterized by lower roughness (Ra parameter was analyzed).…”
Section: Introductionmentioning
confidence: 95%
“…Low thermal conductivity hampers heat transfer from the cutting zone, which impacts the condition of both the machined material as well as the material of which the tool is made. High tensile strength precludes deep cutting [ 3 , 4 ], while the above-mentioned work hardening as a result of plastic deformation requires cutting at a depth greater than the thickness of the work-hardening zone. Studies in this area [ 5 ] confirmed that nickel-based alloys work harden during machining, which is caused by a significant plastic deformation of the front of the blade.…”
Section: Introductionmentioning
confidence: 99%